Design of the DISCovery project: tailored work-oriented interventions to improve employee health, well-being, and performance-related outcomes in hospital care - Niks Irene MW; de Jonge Jan; Gevers Josette MP; Houtman Irene LD (BMC, 2013)
Abstract Background It is well-known that health care workers in today's general hospitals have to deal with high levels of job demands, which could have negative effects on their health, well-being, and job performance. A way to reduce job-related stress reactions and to optimize positive work-related outcomes is to raise the level of specific job resources and opportunities to recover from work. However, the question remains how to translate the optimization of the balance between job demands, job resources, and recovery opportunities into effective workplace interventions. The aim of the DISCovery project is to develop and implement tailored work-oriented interventions to improve health, well-being, and performance of health care personnel. Methods/Design A quasi-experimental field study with a non-equivalent control group pretest-posttest design will be conducted in a top general hospital. Four existing organizational departments will provide both an intervention and a comparison group. Two types of research methods are used: (1) a longitudinal web-based survey study, and (2) a longitudinal daily diary study. After base-line measures of both methods, existing and yet to be developed interventions will be implemented within the experimental groups. Follow-up measurements will be taken one and two years after the base-line measures to analyze short-term and long-term effects of the interventions. Additionally, a process evaluation and a cost-effectiveness analysis will be carried out. Discussion The DISCovery project fulfills a strong need for theory-driven and scientifically well-performed research on job stress and performance interventions. It will provide insight into (1) how a balance between job demands, job resources, and recovery from work can be optimized, (2) the short-term and long-term effects of tailored work-oriented effects, and (3) indicators for successful or unsuccessful implementation of interventions.